A central role for p38 MAPK in the early transcriptional response to stress - Whitmarsh, Alan J (BioMed Central, 2010)
The mitogen-activated protein kinase p38 (p38 MAPK) is activated by a number of stresses. A recent study in BMC Genomics has uncovered the early transcriptional responses to three types of stress and has demonstrated a central role for p38 MAPK in mediating these responses. See research article http://www.biomedcentral.com/1471-2164/11/144